The Contribution of Influencer Marketing, Product Quality, and Online Customer Reviews in Forming Purchase Decisions through Brand Trust as a Mediating Variable in the Local Perfume Brand HMNS Sore X Sheila Dara Variant - Anindia Rachma; Shandy Puspita (JURNAL COMPUTECH & BISNIS, 2026)
This study examines the impact of influencer marketing, product quality, and online customer reviews on purchase decisions, with brand trust serving as a mediating variable for the HMNS perfume variant SORE x Sheila Dara. This study employs a quantitative methodology, utilizing a survey of 255 respondents, which was examined via SPSS and the Sobel test. This study's results demonstrate that these three criteria positively and significantly influence brand trust and purchasing decisions. Brand trust significantly influences buying decisions and mediates the relationships among variables. The findings affirm that brand trust is an essential factor that enhances the efficacy of digital marketing techniques in influencing customer purchase behavior.